State of the Union 2018 (Luxembourg, 2018)
"Every year in September, the President of the European Commission delivers his State of the Union Address before the European Parliament, taking stock of achievements of the past year and presenting priorities for the year ahead. The President also sets out how the European Commission will address the most pressing challenges the European Union is facing. The speech is followed by a plenary debate. This kick-starts the dialogue with the European Parliament and the Council to prepare the Commission Work Programme for the following year. Anchored in the Treaty of Lisbon, the State of the Union Address is set out in the 2010 Framework Agreement on relations between the European Parliament and the European Commission, which also requires the President to send a Letter of Intent to the President of the European Parliament and the Presidency of the Council detailing the actions the European Commission intends to take by means of legislation and other initiatives until the end of the following year. Jean-Claude Juncker, the President of the European Commission, delivered his fourth State of the Union Address on 12 September 2018. All material is available at http://ec.europa.eu/soteu2018. This year's speech comes in the lead up to the 2019 European elections and the ongoing debate about the future of the European Union at 27"